Impact of implementing a multifaceted intervention to reduce rates of cesarean section: A quality‐improvement study. Issue 2 (5th September 2020) - Zahumensky, Jozef; Psenkova, Petra; Dolezal, Pavel; Otapkova, Petra; Papcun, Peter; Ferianec, Vladimir; Krizko, Marian
Abstract: Objective: To assess the impact of a multifaceted intervention on reducing the rate of cesarean section (CS) without negatively affecting the rate of perinatal mortality. Methods: A retrospective analysis of CS was performed before and after the implementation of a quality‐improvement (QI) intervention in a university‐affiliated teaching hospital in the Slovak Republic. All women who gave birth in 2015 (pre‐intervention) and 2018 (post‐intervention) were included. The different components of the intervention were introduced from September 2016. The main outcome was the overall rate of CS. A subanalysis by Robson groups was undertaken. Results: After the implementation of the QI intervention, there was a 33.5% reduction in the rate of CS compared to the pre‐intervention period where the rate reduced from 33.7% to 22.4% ( P <0.001; relative risk 0.66, 95% confidence interval [CI] 0.61–0.72; Number Needed to Treat (NNT) 8.8, 95% CI 7.3–11.2). The main contributors were the reduction in elective CS for non‐obstetric reasons, a reduction in intrapartum CS for failure to progress, and an increase in the number of vaginal births after CS in the post‐intervention period. Conclusion: The implementation of the composite QI intervention led to a significant reduction in the rate of CS without affecting the rate of perinatal mortality. Abstract : This study demonstrates the effectiveness of a composite evidence‐based quality‐improvement intervention on reducing the rate of cesarean section without affecting the rate of perinatal mortality.